Análise econômica das normas concedentes de incentivos fiscais e sua aptidão para prover direitos sociais: um estudo sobre a eficiência do PRODESIN - Barbosa , Bruno Sarmento (2014)
Tax incentives are used by states as the solution for all social and economic problems. However there is not an appropriate analysis of the particularities of each entity of the federation, or in relation to the impact of tax relief. It is known that the rights have costs and these costs are borne by society. States should take this fact into account to adopt measures to encourage and benefit businesses as a way to attract them. A standard that provides incentives to be considered must be able to efficiently induce the behavior of corporations, and create conditions for the vocations of the state to be developed and encouraged with the necessary consequence that is an effective return on storage, as well as an evolution in economic and social indicators of citizens who bear the costs of the incentives. In this scenario the pragmatic method, future-oriented, concerned about the consequences of the public choices, judicial decisions and legal standards, is useful and recommended for analysis and advice on the adoption of incentive measures. In this sense , it is adopted in this work the pragmatism developed by Richard Posner worried about the practical consequences of the measures taken, supports the application of the apparatus of economics as a way to assist the law. Posner believes that the law should be more empirical and that the economy has the tools to do so. In this sense , this work will make an Economic Analysis of Law . 5.671/95, from the State of Alagoas, which established the Integrated Development Program - PRODESIN in order to assess if the law has been alluded to and is It is able to achieve the goals it has set itself and if it is efficient to the point, in the weighing costs imposed on society by the exemptions and benefits expected to bring the state an effective progress in economic and social indicators.